α-Synuclein is required for sperm exocytosis at a post-fusion stage - Buzzatto, Micaela Vanina; Berberián, María Victoria; Di Bartolo, Ary Lautaro; Masone, Diego; Tomes, Claudia Nora (Frontiers in Cell and Developmental Biology, 2023)
Sperm contain a large dense-core secretory granule (the acrosome) whose contents are secreted by regulated exocytosis (the acrosome reaction, AR) at fertilization through the opening of multiple fusion pores between the acrosomal and plasma membranes. In other cells, the nascent pore generated when the membrane surrounding a secretory vesicle fuses with the plasma membrane may have different fates. In sperm, pore dilation leads to the vesiculation and release of these membranes, together with the granule contents. α-synuclein is a small cytosolic protein claimed to exhibit different roles in exocytic pathways in neurons and neuroendocrine cells. Here, we scrutinized its role in non-neuronal cells. Western blot reveals the presence of α-synuclein and indirect immunofluorescence its localization to the acrosomal domain of unreacted human sperm. Despite its small size, the protein is retained following permeabilization of the plasma membrane with streptolysin O. Antibodies to human α-synuclein halt calcium-triggered secretion when introduced after docking into permeabilized cells. Two functional assays, fluorescence and transmission electron microscopies indicate that the secretion blockage is due to the stabilization of open fusion pores. At this point, synaptobrevin is insensitive to neurotoxin cleavage because it is engaged in post-fusion, cis SNARE complexes. Recombinant α-synuclein rescues the inhibitory effects of the anti-α-synuclein antibodies and of a chimeric Rab3A-22A protein that also inhibits the AR after fusion pore opening. Restrained molecular dynamics simulations show that the energy cost of expanding a nascent fusion pore between two model membranes is lower in the presence than in the absence of α-synuclein. Hence, our results suggest that α-synuclein is essential for the expansion of fusion pores.